2020
DOI: 10.1029/2020gl087119
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ancient Dissolved Organic Carbon in Arctic Ocean Sediment: A Pathway of Carbon Cycling in the Extreme Environment

Abstract: We report quantitative carbon isotope evidence showing that porewater dissolved organic carbon (DOC) is produced from different sources in Arctic Ocean sediments, resulting in dramatic changes in both δ13C and Δ14C values of DOC. The very low δ13C (−42.7‰) and Δ14C (−947‰) values measured for porewater DOC indicate that bacteria consume methane hydrate‐derived OC and convert a significant fraction of this δ13C depleted and old OC (44–97%) into DOC in the sediments of the Arctic Ocean. We suggest that the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…1). The degradation of clam tissues would also lead to the increase of pore water DIC content 30 , which is possibly one main driver of Hg methylation as it in uences both Hg bioavailability and microbial activities 31 .…”
Section: Resultsmentioning
confidence: 99%
“…1). The degradation of clam tissues would also lead to the increase of pore water DIC content 30 , which is possibly one main driver of Hg methylation as it in uences both Hg bioavailability and microbial activities 31 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been shown that the N and/or P limitation in the subtropical gyres can enhance DOC production by phytoplankton (Moreno & Martiny, 2018;Zakem & Levine, 2019). In the Arctic Ocean, observations (Bussmann & Kattner, 2000;Engel et al, 2019;Fu et al, 2020;Hansell et al, 2004) also suggest that our model underestimates the surface Arctic DOC concentrations by around 30 mmol C/m (Figure 4). This is not surprising as previous studies (Connolly et al, 2020) have shown a strong influence of the relatively refractory terrestrial DOC supplied to the Arctic Ocean by rivers, a component of DOC that is not represented in our model.…”
Section: Fe Doc and Fl Bacteria Biomass And Productionmentioning
confidence: 66%
“…2 ) in the Japan Trench are ~6 times higher than those in other oceanic trenches 20 and increase with depth, reaching maximum concentrations (Fig. 2 ) that are comparable to the coastal 21 and continental shelf 22 areas, highlighting a dynamic carbon cycle and huge dissolved carbon storage in the hadal trenches enhanced by earthquakes.
Fig.
…”
Section: Results and Discussionmentioning
confidence: 87%